Super Imperialism : The Origin and Fundamentals of U.S. World Dominance - Hudson, Michael, 1939- (London Pluto Press, 2003)
Investigates the genesis of the US's political and financial domination of today's economic system. 'One of the most important books of this century.' Terence McCarchy, Columbia University.
Include Index
Keywords: United States -- Diplomatic relations -- International economic relations